Economists, Incentives, Judgment, and Empirical Work - David C. Colander (Kiel Institute for the World Economy (IfW), 2008)
This paper asks the question: Why has the ?general-to-specific? cointegrated VAR approach as developed in Europe had only limited success in the US as a tool for doing empirical macroeconomics, where what might be called a ?theory comes first? approach dominates? The reason this paper highlights is the incompatibility of the European approach with the US focus on the journal publication metric for advancement. Specifically, the European ?general-to specific? cointegrated VAR approach requires researcher judgment to be part of the analysis, and the US focus on a journal publication metric discourages such research methods. The US ?theory comes first? approach fits much better with the journal publication metric.
Keywords: B4; 330; Incentives; empirical work; econometrics; methodology; cointegration; VAR; Wirtschaftsforschung; Ökonometrie; Wissenschaftliche Methode; Vergleich; Motivation; Publikationsanalyse; Vergleich; Wirtschaftsmodell; USA; VAR-Modell; Kointegration; Europa